Legal protection for vocational school students undertaking practical work experience during the pandemic - Haryanti, Amelia; Santoso, Bambang; Dindin, Dindin (Universitas Negeri Yogyakarta, 2023)
Fieldwork practice for class XI learners in Vocational Intermediate Schools is a mandatory activity that must be carried out; this is done so that learners are ready to compete in the world of work after graduation following their chosen interests. Although currently in the covid-19 pandemic, fieldwork practices must still be implemented. One of the consent clauses between the school and the parents/guardians of learners mentions that parents/guardians cannot sue the school or company if, during fieldwork practice activities, learners are exposed to the covid-19 virus or have a work accident. The method used in this study uses qualitative descriptive methods, this study aims to find out, how legal protection for learners during the implementation of street vendors in the covid-19 pandemic period is reviewed from law No. 13 of 2003 on Employment and what rights are received by learners during the PKL activities reviewed from Law No. 35 of 2014 on Child Protection. From the results of the research obtained that the form of protection carried out by the school and companies where fieldwork practices are guiding and supervising during this activity, while the rights received by learners in addition to getting grades as a condition of graduation, they also gain experience working directly on the field to be able to compete in the world of work after graduating vocational.